IGlarLixi reduces residual hyperglycemia in Japanese patients with type 2 diabetes uncontrolled on basal insulin: A post‐hoc analysis of the LixiLan JP‐L trial. Issue 11 (19th June 2021) - Yabe, Daisuke; Iizuka, Katsumi; Baxter, Mike; Watanabe, Daisuke; Kaneto, Hideaki
Abstract: Introduction: Treatments for type 2 diabetes targeting baseline glucose levels but not postprandial glucose can result in normalized fasting blood glucose but suboptimal overall glycemic control (high glycated hemoglobin): residual hyperglycemia. In Japanese patients with type 2 diabetes the predominant pathophysiology is a lower insulin secretory capacity, and residual hyperglycemia is common with basal insulin treatment. Single‐injection, fixed‐ratio combinations of glucagon‐like peptide‐1 receptor agonists and basal insulin have been developed. iGlarLixi (insulin glargine 100 units/mL [iGlar]: lixisenatide ratio of 1 unit:1 µg) is for specific use in Japan. Post‐hoc analysis of the LixiLan JP‐L trial (NCT02752412) compared the effect of iGlarLixi with iGlar on this specific subpopulation with residual hyperglycemia. Materials and Methods: Outcomes at week 26 (based on the last observation carried forward) were assessed in patients in the modified intent‐to‐treat population with baseline residual hyperglycemia. Results: Overall, 83 (32.5%) patients in the iGlarLixi group and 79 (30.7%) patients in the iGlar group had baseline residual hyperglycemia. The proportion of patients with residual hyperglycemia at week 26 decreased to 15.7% in the iGlarLixi group, and increased to 36.9% in the iGlar group. Patients in the iGlarLixi group had significantly greater reductions in glycated hemoglobin compared with the iGlar group (−0.72% difference between groups; P < 0.0001). Conclusions: New data from this post‐hoc analysis of the JP‐L trial show that treatment with the fixed‐ratio combination iGlarLixi reduced the proportion of Japanese patients with residual hyperglycemia from baseline to week 26 and significantly reduced glycated hemoglobin vs similar doses of iGlar alone. Abstract : In Japanese patients with type 2 diabetes, the predominant pathophysiology is a low insulin secretory capacity, and residual hyperglycemia is common with basal insulin treatment. iGlarLixi is a single‐injection, fixed‐ratio combination of a glucagon‐like peptide‐1 receptor agonist and basal insulin developed specifically for use in Japan, and investigated in the LixiLan JP‐L trial. In this post‐hoc analysis of the JP‐L trial, treatment with iGlarLixi reduced the proportion of Japanese patients with residual hyperglycemia from baseline to week 26 and significantly reduced HbA1c compared with treatment with comparable doses of basal insulin alone.